Pengaruh Fitur Layanan Dan Keamanan Terhadap Kepuasan Nasabah Menggunakan Mobile Banking Pada Bank Syariah Indonesia Kc Palembang Demang Dengan Kepercayaan Sebagai Variabel Intervening - Fadhilah Oktariani; Maya Panorama; Muhamad Rahman Bayumi (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research aims to analyze or find out how Service and Security Features influence Customer Satisfaction using Mobile Banking with Trust as an intervening variable at Bank Syariah Indonesia KC Palembang Demang because not all customers think that service features are able to make customers feel satisfied with online transactions provided by the party. BSI. This research uses quantitative methods. The population in this study are customers who use BSI mobile banking with the total number of customer information obtained from BSI Demang being 13,584 users. This research uses primary data through the distribution of questionnaires distributed to 99 respondents, then analysis is carried out using the Structural Equation Model (SEM). The results of the data analysis test show that the Service Feature variable does not have a positive and significant effect on customer satisfaction when using mobile banking at Bank Syariah Indonesia KC Palembang Demang. The Security variable has a positive and significant effect on Customer Satisfaction using mobile banking at the Indonesian Sharia Bank KC Palembang Demang. The Trust variable has a positive and significant effect on Customer Satisfaction using mobile banking at the Indonesian Sharia Bank KC Palembang Demang. The Service Feature variable has a positive and significant effect on customer trust in using mobile banking at the Indonesian Sharia Bank KC Palembang Demang. The security variable has a positive and significant effect on customer trust in using mobile banking at the Indonesian Sharia bank KC Palembang Demang. The Trust variable is able to mediate Service Features on Customer Satisfaction using mobile banking at Bank Syariah Indonesia KC Palembang Demang. The Customer Trust variable is able to mediate Security and Customer Satisfaction using mobile banking at Bank Syariah Indonesia KC Palembang Demang